(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Acute pancreatitis (AP) is a life-unpleasant situation with contradictory and inadequate treatments. In this regard, the present study evaluated the effect of the possible pretreatment of lipase-pancreatin on L-arginine-induced AP. Forty adult mice were selected and divided into five groups: I) control group, II and III) AP groups (i.p.) receiving L-arginine of 2×300 and 2×400 mg/100 g body weight (b.w.), IV) AP (2×300 L-arginine) group + pancreatin (mice were i.p. injected by 350 U-lipase), and V) AP (2×400 L-arginine) group + pancreatin (mice were i.p. injected by 350 U-lipase). All AP groups displayed a significant increase in serum levels of ALT, AST, TBARS, and TNF-alpha compared to the control group. Moreover, pancreatic tissue edema, inflammation, and vacuolization of acinar cells were significantly higher in the untreated L-arginine group compared to the control and pancreatin groups. Conversely, the diameter of pancreatic islets significantly declined after induction of pancreatitis compared with control and pancreatin groups. Pancreatin treatment can be used in pancreatic dysfunction, however, this medicine showed no protective effect against L-arginine-induced AP in the mouse model.